Muscle‐tendon architecture in Kenyans and Japanese: Potential role of genetic endowment in the success of elite Kenyan endurance runners. (17th April 2022) - Kunimasa, Yoko; Sano, Kanae; Oda, Toshiaki; Nicol, Caroline; Komi, Paavo V.; Ishikawa, Masaki
Abstract: Aim: The specificity of muscle‐tendon and foot architecture of elite Kenyan middle‐ and long‐distance runners has been found to contribute to their superior running performance. To investigate the respective influence of genetic endowment and training on these characteristics, we compared leg and foot segmental lengths as well as muscle‐tendon architecture of Kenyans and Japanese males (i) from infancy to adulthood and (ii) non‐athletes versus elite runners. Methods: The 676 participants were divided according to their nationality (Kenyans and Japanese), age (nine different age groups for non‐athletes) and performance level in middle‐ and long‐distance races (non‐athlete, non‐elite and elite adult runners). Shank and Achilles tendon (AT) lengths, medial gastrocnemius (MG) fascicle length, pennation angle and muscle thickness, AT moment arm (MAAT ), and foot lever ratio were measured. Results: Above 8 years old, Kenyans had a longer shank and AT, shorter fascicle, greater pennation angle, thinner MG muscle as well as longer MAAT, with lower foot lever ratio than age‐matched Japanese. Among adults of different performance levels and independently of the performance level, Kenyans had longer shank, AT and MAAT, thinner MG muscle thickness, and lower foot lever ratio than Japanese. The decrease in MG fascicle length and increase pennation angle observed for the adult Japanese with the increase in performance level resulted in a lack of difference between elite Kenyans and Japanese. Conclusion: The specificity of muscle‐tendon and foot architecture of elite Kenyan runners could result from genetic endowment and contribute to the dominance of Kenyans in middle‐ and long‐distance races.